2024
DOI: 10.1016/j.rcp.2021.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Mood and Sleep Quality in Peruvian Medical Students During COVID-19 Pandemic

Abstract: Introducción: La prolongación y consecuencias que dejó la pandemia del covid-19 genera un panorama incierto y devastador en muchas poblaciones, la evidencia muestra una alta prevalencia de problemas de salud mental en estudiantes de medicina. Objetivo: El objetivo del estudio fue evaluar la asociación entre los trastornos del estado de ánimo y la calidad del sueño (SQ) en estudiantes de medicina peruanos durante la pandemia de COVID-19. Métodos: Se realizó un estudio transversal en 310 es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
7

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
1
13
0
7
Order By: Relevance
“…This study used the PSQI to identify factors associated with poor sleep quality in medical students, and demonstrated that the incidence of poor sleep quality was 31.9%. This figure is consistent with many previous studies (Johnson et al, 2017;Eleftheriou et al, 2021;Gupta et al, 2021;Olarte-Durand et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…This study used the PSQI to identify factors associated with poor sleep quality in medical students, and demonstrated that the incidence of poor sleep quality was 31.9%. This figure is consistent with many previous studies (Johnson et al, 2017;Eleftheriou et al, 2021;Gupta et al, 2021;Olarte-Durand et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…As the university students experienced frequent lockdown, quarantine, and accommodation relocations during the Covid-19 pandemic, their experience of depression, anxiety, negative emotions, and attention incapacity increased, which were threatening their mental health 49 , 50 , 51 , 52 . Sleep difficulties and mood disturbance became more prevalent than before because of the Covid-19 pandemic 53 , 54 , 55 . Incorporating outdoor walking in nature with mindfulness practise was assumed to improve university students’ sleep quality and mood.…”
Section: Discussionmentioning
confidence: 99%
“…This result is higher than estimates found in meta-analyses during (47%, 95% CI = 35-59%) and before (34%, 95% CI: 29-39%) the pandemic period [20]. Prevalence of anxiety symptoms was unexpectedly higher than prior Peruvian studies (36-57%) conducted during the first wave in Peru [44][45][46][47]. However, as with depression scores, differences between estimates are related to the instrument used (e.g., GAD-7, DASS-21, BAI-21), different cut-off values, and the study period.…”
Section: Plos Onementioning
confidence: 60%
“…Although PHQ-9 was used, both studies have unclear information about how education was delivered. Another study found a prevalence of 60% with DASS-21 [ 46 ], but data collection period was after the first wave and possibly online education was delivered. Another notable finding is the 37% prevalence reported during suspension of classes [ 47 ], suggesting that academic courses increase the presence rate of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%